אתה יכול להתחיל על ידי רציונליזציה:
# (sqrt (1 + x) + sqrt (1-x)) / (sqr (1 + x) -qqrt (1-x)) × (sqrt (1 + x) + sqrt (1-x)) / sqrt (1 + x) + sqrt (1-x)) = #
# = (sqr (1 + x) + sqrt (1-x)) ^ 2 / (2x) = #
# (1 + x) + 2sqrt (1 + x) sqrt (1-x) + (1-x)) / (2x) = #
# = (2 + 2sqrt (1-x ^ 2)) / (2x) = #
# = (1 + sqrt (1-x ^ 2)) / (x) = #
תחליף: # x = sqrt (3) / 2 # אתה מקבל:
# 1 (1 + sqrt (1-3/4)) / (sqrt) 3/2) = (1 + 1/2) * (2 / sqrt (3)) = #
# 3 = 3/2 * 2 / sqrt (3) = 3 / sqrt (3) = 3 / sqrt (3) * sqrt (3) / sqrt (3) = sqrt (3)
מקווה שזה מה שאתה צריך! Youנות